2003
DOI: 10.1590/s0006-87052003000100014
|View full text |Cite
|
Sign up to set email alerts
|

Adsorção de fósforo em solos de argila de atividade baixa

Abstract: Neste estudo foram avaliadas possíveis correlações entre atributos físicos e químicos do solo e a capacidade máxima de adsorção de fósforo (CMAP) em solos com argila de atividade baixa de diferentes regiões do Brasil, sendo utilizadas amostras de horizontes superficiais (A) e subsuperficiais (B) de 16 perfis de solos. As doses para a determinação da CMAP foram calculadas com base no teor de fósforo remanescente e variaram de 0 a 135 mg.L-1. A partir dos dados obtidos foram então construídas isotermas de adsorç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
32

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 14 publications
(4 reference statements)
2
18
0
32
Order By: Relevance
“…These results strengthen the hypothesis that P adsorption is only affected by the quality of OM in the soil, not only because OM competes with phosphate ions for adsorption sites (Mesquita Filho & Torrent, 1993;Heredia & Cirelli, 2007), but also because it provides pedoenvironmental conditions that potentially affect the dynamics of pedogenic iron oxides (Kämpf & Curi, 2000) by favoring their main reactions: dissolution, reduction, and complexation (Schwertmann, 1991;Silva Neto et al, 2008). Valladares et al (2003) examined P adsorption in soils with low clay activity and found that those with a clayey texture adsorb higher amounts of P. Our highest P ads levels were those of the soils with the lowest clay contents (Table 1), which strengthens the hypothesis that the quality of the clay is as influential as or even more so than its content in the soil (particularly in highly clayey, weathered soils).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…These results strengthen the hypothesis that P adsorption is only affected by the quality of OM in the soil, not only because OM competes with phosphate ions for adsorption sites (Mesquita Filho & Torrent, 1993;Heredia & Cirelli, 2007), but also because it provides pedoenvironmental conditions that potentially affect the dynamics of pedogenic iron oxides (Kämpf & Curi, 2000) by favoring their main reactions: dissolution, reduction, and complexation (Schwertmann, 1991;Silva Neto et al, 2008). Valladares et al (2003) examined P adsorption in soils with low clay activity and found that those with a clayey texture adsorb higher amounts of P. Our highest P ads levels were those of the soils with the lowest clay contents (Table 1), which strengthens the hypothesis that the quality of the clay is as influential as or even more so than its content in the soil (particularly in highly clayey, weathered soils).…”
Section: Resultssupporting
confidence: 71%
“…Phosphorus adsorption in soil depends markedly on the content and crystallinity of iron oxides, as well as on the content and quality of OM, which can compete with phosphate ions for sorption sites (Mesquita Filho & Torrent, 1993;Heredia & Cirelli, 2007). As a rule, organic substances convert positive charges at active sites in clay minerals and oxides into negative charges, thereby potentially reducing P adsorption (Valladares et al, 2003). Novais & Smyth (1999) studied P adsorption in Latosols (Oxisols) from the Brazilian cerrado (tropical savannah) which adsorbed more than 2 mg cm -3 P (equivalent to 4000 kg ha -1 P or 9200 kg ha -1 P 2 O 5 ) in the 0-0.20 m layer.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Rolim Neto et al (2004), nos Latossolos estudados em seu experimento, com texturas e materiais de origem variável, a proporção e a área superficial da gibsita e goethita tiveram participação destacada na adsorção de P. Valladares et al (2003) encontraram correlação da CMAP e do teor de argila, ou seja, duas características que aumentam o poder tampão de fosfato dos solos e, consequentemente, afetam o poder de extração de determinados extratores. Silva et al (2004) demonstraram a influência da argila na adsorção de P; desta forma, os extratores Mehlich-1, Mehlich-3 e Bray-1 se correlacionaram com ambas as características, evidenciando a sua importância na taxa de recuperação dos extratores, que poderá ser fundamental na sua capacidade em predizer a disponibilidade de P; por outro lado, a RTI não apresentou correlação significativa em nenhuma das características avaliadas, corroborando com o trabalho realizado por Silva & Raij (1999), que descreveram a RTI como sendo o melhor extrator para os mais variados tipos de solo.…”
Section: Dunclassified
“…Plant P availability is also hampered in highly weathered soils, such as tropical soils, that are usually acidic with a high potential of iron and aluminum oxides to absorb P (Valladares et al, 2003;Raij, 2004;Hopkins and Ellsworth, 2005). This strong interaction with the soil is why P is applied at the highest rates to crops in tropical areas (Rao et al, 1999).…”
Section: Introductionmentioning
confidence: 99%